Calendario de siembra para La Pampa - Huespe, Daiana Susana; Melis, Omar Alejandro; Angeleri, Carolina Adriana; Muguiro, Alberto; Weinmeister, Soledad Analía; Etchart, Francisco Aníbal (Ediciones INTA, 2021)
Póster